The Relationship Between Interpersonal Communication and Peer Social Support in Overseas Students - Fadila Oktavianti; Jihan Nabilah Saper; Shelvia Eka Yusida; Ghazy Agil Saleh (CV. Doki Course and Training, 2024)
Students are able to build communication between peers through social support around them by building interpersonal communication especially for students who are far from their university hometown. In this case we will discuss whether interpersonal communication affects social support especially for students who are far from the city of origin of their education. This study aims to determine the relationship between interpersonal communication and peer social support in overseas students. The study population amounted to 30 students. The sample in this study used quantitative correlation method. The data collection method uses a 20 item scale of interpersonal communication and 20 items of peer social support. Data were analyzed using simple regression analysis. The analysis results show the value (rxy) = 0.581 with p = 0.001 (p <0.05), meaning that there is a positive relationship between variables X and Y by 33.7%.